Outdoor Narrowband Measurements in 800 MHz Band for PPDR Private Networks - Victor Fernandes; Alberto G. Guimarães; Pedro V. G. Castellanos (Journal of Microwaves, Optoelectronics and Electromagnetic Applications)
Abstract In this work, we investigated the path loss (PL) profile of the outdoor radio channel in the 800 MHz band for the Icaraí region in the city of Niterói. This frequency band has recently been reserved by the brazilian National Telecommunications Agency (ANATEL) for utilization in Public Protection and Disaster Relief (PPDR) wireless networks, and Icaraí constitutes a potential area to receive coverage provided by a PPDR network whose implementation is of interest to the Niterói government. The investigation relies on narrowband large scale measurements, recorded at various places throughout the neighborhood. As a theoretical framework for the analysis, we consider four log-distance PL models, which have been widely used in recent outdoor channel sounding works. Our findings seek to facilitate the successful establishment and optimization of PPDR networks in Niterói city.